Who knew - Diller, Barry (Simon & Schuster, 2025)
"Growing up in Beverly Hills, Diller was neglected by his parents, abused by his brother, and overwhelmed by insecurity. Diller began his career in the mailroom of the William Morris Agency and had one of the most extraordinary ascents in show business history, inventing the TV Movie of the Week for ABC at age twenty-seven, becoming CEO of Paramount Pictures at age thirty-two, and launching the Fox TV network at age forty-four. . . . Diller shares his provocative and at times counterintuitive insights about advancing in a company; becoming a manager and a leader; and the value of confrontation. He describes his relentless quest for good ideas along with what he learned from the bad ones. For the first time, Diller also tells the story of his unconventional and very private personal life, describing relationships with men and the woman he calls his 'unique and complete love,' designer Diane von Furstenberg. Diller writes, 'I would have secrets, but I would tell no lies""--Excerpted from Inside jacket flap.